2014
DOI: 10.1007/s00127-014-0871-7
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and disclosing one’s mental illness to family and friends

Abstract: Anticipated discrimination as an external threat and stigma-related stress as an internal process may reduce comfort with disclosure and could be targeted in interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
3
38
2
3
Order By: Relevance
“…Conversely, it has been reported that greater comfort in disclosing one's mental illness was associated with lower anticipated discrimination [23].…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, it has been reported that greater comfort in disclosing one's mental illness was associated with lower anticipated discrimination [23].…”
Section: Discussionmentioning
confidence: 96%
“…Perceived stigma was negatively correlated with disclosure in one study (Bos et al, 2009) and positively correlated with secrecy in four studies (Chronister et al, 2013;Kleim et al, 2008;O'Mahen et al, 2011;Yow & Mehta, 2010). Anticipated discrimination was negatively correlated with comfort about disclosing in one study (Rüsch et al, 2014).…”
Section: Factors Associated With Disclosure and Concealment In Quantimentioning
confidence: 93%
“…In line with previous research (Corrigan, 2004;Sartorius, 2007;Schomerus & Angermeyer, 2008), self-stigma was associated with reluctance to disclose and seek help. Some studies have concluded that, in the general population, individuals are less likely to disclose more heavily stigmatized mental health problems (psychosis, bipolar disorder, addiction) compared with less stigmatized ones (depression, anxiety, eating disorders), owing to higher levels of anticipated discrimination (Rüsch, Brohan, Gabbidon, Thornicroft, & Clement, 2014). In contrast, a review on workplace disclosure concluded that lower levels of disability resulting from the respective mental health problem together with higher concealability are negatively associated with workplace disclosure (Brohan et al, 2012).…”
Section: Stigma Disclosure and Help-seekingmentioning
confidence: 99%